Développement durable, contestation et légitimité : la perspective des mouvements altermondialistes - Carlos R. S. Milani; Chloé Keraghel (Cahiers des Amériques Latines)
Criticisms on the non-binding results of the Rio 1992 political process in promoting sustainable development include acknowledging that the current global economic model is unable to solve the social and environmental problems which it generates itself. Thus it is not surprising that transnational contestatory movements have been trying to redefine themselves the politics of sustainable development taking into account the diversity of voices, the production of counter-expertise, and the dissemination of alternative scientific reports. Alter-globalist movements question sustainable development mainstream while criticising an economicist model that is said to neglect cultural diversity and the particularities of local economies and histories. This article analyses the role of alter-globalist movements in the reformulation of the political agenda within the field of sustainable development.